Embryo transfer in cattle in the Carchi province - Chugá Bastidas, Wilson Santiago; Martínez Chugá, Rubén Dario; Cerón Villarreal, Stalin Mauricio; Játiva Cortez, Dagmar Nataly; Chamorro Pantoja , Brayan; Chirán Ayala, Gladys Yesenia; Balarezo Urresta, Luis Rodrigo; Proaño Deleg, Miguel Augusto (SATHIRI, 2021)
The Superovulatory response and the conception rate were evaluated by applying the non-surgical technique of embryo transfer in heifers, from the Santa Clara and San Francisco farms in the province of Carchi. A donor cow of high genetic value was chosen, the same one that was subjected to super-ovulation, through the application of a hormonal protocol for seven days, from day eight the application of the protocol for synchronization of estrus was started, to day ten insemination is done. The selection of eight vaconas was done, the same ones that were prepared to serve as recipients, the synchronization protocol lasted ten days, the application of the protocols was programmed to synchronize the donor with the receivers. On the fifteenth day, the embryos were extracted by washing, the same day in the laboratory the viable embryos were selected, obtaining as a result two with the quality characteristics, they were prepared and transferred immediately in the heifers, which after the gynecological check they were chosen as receivers (Adela) of Santa Clara farm and (Gema) of San Francisco farm.
Keywords: Superovulatory; protocol; embryos; synchronization